2000
DOI: 10.1055/s-2000-9230
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathia centralis serosa - Magengeschwür der Augenheilkunde?

Abstract: Centralis serosa retinopathy is regarded in ophthalmology as a psychosomatic disease, although this assumption has not been satisfactorily proven so far. With the use of the Freiburg Personality Inventory (FIP, [4]), the questionnaire for the evaluation of psychosomatic pathological processes [10], and by recording the affliction undergone by stressful events in the patients' lives, the question as to whether a psychogenic contributory cause existed was examined with a control group study (n = 11), parallelise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
1
4
0
3
Order By: Relevance
“…[11][12][13] This was also shown by the patients in our sample, who, however, were particularly spontaneous and flexible as well. These results may permit the hypothesis that these are personalities in whom openness and spontaneity on the one hand and insecurity on the other hand can give rise to inner conflicts.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…[11][12][13] This was also shown by the patients in our sample, who, however, were particularly spontaneous and flexible as well. These results may permit the hypothesis that these are personalities in whom openness and spontaneity on the one hand and insecurity on the other hand can give rise to inner conflicts.…”
Section: Discussionsupporting
confidence: 75%
“…11 Altogether, the problem remains that investigations of CSC with a prospective study design, such as our own study, only attain small case numbers because the ailment is so rare. [11][12][13] All the studies with larger samples between 50 and 350 patients were conducted as retrospective investigations, leading to considerable methodological difficulties in establishing modification sensitive psycho-ophthalmological parameters. 15-17 25 The significance of the psychosomatic aspects of CSC, in the light of the results of our own study and those reported in previous literature, remains inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zur Beantwortung dieser Fragen wurde mit einer bibliometrischen Analyse der letzten beiden Jahrgänge der PPMP geprüft, a) in welchem Verhältnis die Fachdisziplinen in der PPMP repräsentiert sind, b) ob sich die Beiträge von Psychiatern, Psychosomatikern/Psychotherapeuten und Medizinpsychologen hinsichtlich der Zitiergewohnheiten, des Sprachstils (kognitives Prägnanzniveau) und der Leitfiguren (Repräsentanten spezifischer wissenschaftlicher Paradigmen oder Ansätze) unterscheiden, c) wie häufig die Autoren der PPmP im Jahrgang 2000 im ¹Science-Citation-Indexª (SCI) und ¹Social-Sciences-Citation-Indexª (SSCI) gelistete und impaktfaktornotierte (Impaktfaktor ³ 0,001) Zeitschriften rezipiert haben (Homogenität der [18], Brosig [19], Büsing [20], Dahlbender [21], Fenner [22], Franz [23], Frei [24], Fritzsche [25], Geiser [26], Gündel [27], Häfner [28], Häuser [29], Henningsen [30], Herpertz S. [31,32], Hessel [33], Huber [34], Jacubeit [35], Johann [36], Junkert-Tress [37], Jurkat [38] Aufschlussreich ist in diesem Zusammenhang auch die Betrachtung, welche einzelnen Artikel in der PPmP in den letzten 22 Jahren von der Fachwelt am häufigsten zitiert wurden (Tab. 7).…”
Section: Stichprobe Und Methodeunclassified